PORTARIA PRBA N° 258, DE 13 DE AGOSTO DE 2019 - Fabio Conrado Loula (DMPF-e-Administrativo, n. 158, 21/8/2019, p.61-63., 2019)
Designa os Procuradores para atuarem em substituição. Oliveiros Guanais de Aguiar Filho, Nara Soares Dantas Kruscheswsky, André Luiz Batista Neves, Danilo José Matos Cruz, Bartira Araujo Goes, Ruy Nestor Bastos Mello, Vanessa Cristina Gomes Previtera Vicente, Flávia Galvão Arruti, Ana Paula Carneiro Silva, Edgard de Almeida Castanheira, Leandro Bastos Nunes, Edson Abdon Peixoto Filho, Domenico D'Andrea Neto, Caroline Rocha Q. Villas Boas, Juliana de Azevedo Moraes, Mirella de Carvalho Aguiar, Ovídio Augusto Amoedo machado, Fábio Conrado Loula, Cláudio Alberto Gusmão Cunha. Período: 02/09/2019 a 30/09/2019.